Emergency Training, Education And Perceived Clinical Skills For Tsunami Care Among Nurses In Banda Aceh, Indonesia - Husna, Cut; Hatthakit, Urai; Chaowalit, Aranya (Department of Nursing, Faculty of Medicine, Diponegoro University, 2011)
Background: Nurses are a part of health care provider who has responsibility to respond to disaster. The nurses ought to have sufficient knowledge and skills in caring for patients in disasters such as in a tsunami. Clinical skills of nurses effectively help the nurses in handling the tsunami emergency response.Objectives: To describe the levels of perceived clinical skills for tsunami care in acute response phase (6 months) after tsunami struck, and to examine the relationship between emergency training, education, and perceived clinical skills for tsunami care in Banda Aceh, Indonesia.Methods: This was a correlational study. Systematic random sampling was employed to recruit 97 nurses in a hospital in Banda Aceh, Indonesia. Data were collected using questionnaires developed by the researchers and colleagues. The questionnaires consisted of two main parts: The Demographic Data Questionnaire (DDQ) and The Tsunami Care Questionnaire (TCQ).Results: Overall, perceived clinical skills for tsunami care were at a moderate level with the total mean score of 3.52 (SD = 0.86). Pearson product moment correlation coefficients indicated significant relationships between perceived clinical skills for tsunami care and attending emergency training and education (r = .23, p< .05).Conclusion: The nurses in the hospital should maintain and improve their knowledge and skills by regularly attending emergency training and education in order to respond to disaster more effectively.Keywords: Education and perceived clinical skills, tsunami care, nurses